Step-by-step explanation:
[tex] {x}^{2} + 4x = - {y}^{2} + 6[/tex]
[tex] {x}^{2} + 4x + {y}^{2} - 6 = 0[/tex]
Standard Form of Conic is
[tex]ax {}^{2} + bxy + c{y}^{2} + dx + ey + f = 0[/tex]
In this scenario, a is 1. c is 1 d is 4 and f is -6
Since a=c, we will get a circle.
Standard form of a circle is
[tex] (x - h) {}^{2} + (y - k) {}^{2} = {r}^{2} [/tex]
where (h,k) is the center and r is the radius.
Step 1: Convert x^2+4x+y^2-6 into circle.
[tex] {x}^{2} + 4x + {y}^{2} - 6[/tex]
Add 6 to both sides
[tex] {x}^{2} + 4x + {y}^{2} = 6[/tex]
Complete the square with respect to x variable
Divide 4 by 2 and square it, then add that to both sides
[tex]( \frac{4}{2} ) {}^{2} = 4[/tex]
So add four to both sides
[tex] {x}^{2} + 4x + 4 + {y}^{2} = 6 + 4[/tex]
Remebrr that a perfect square is
[tex] {a}^{2} + 2ab + {b}^{2} = (a + b) {}^{2} [/tex]
So we get
[tex](x + 2) {}^{2} + {y}^{2} = 10[/tex]
That is our standard equation.
Look at the graph above.